Women on boards and firm performance: Malaysian evidence - Raja Kamaruzaman, Raja Nur Syazwani; Ahmad, Maslina; Annuar, Hairul Azlan (2016)
There are many studies in developed countries that show positive relationship between the presence of women in top management and firm financial performance. This maybe due to the number of educated women who join the workforce and hold top executive positions in organisations in these countries has increased steadily. Nevertheless, the participation of women in board directorships is still low, particularly in the Asean region despite more of them being better educated. In 2011, the Malaysian cabinet approved the policy that all board of directors of companies listed on the Bursa Malaysia should consist of 30% women in decision-making positions by the year 2016. This study therefore examines the association between the presence of women on the board and firms’ performance following the introduction of diversity policy. The analysis uses information of the top 200 Malaysian public listed companies for the financial year 2011 to 2013. The multiple regression analysis is used to estimate the relationship between the firm performance (ROA) as the dependent variable and the independent variables. The results show that during the period under study, the proportion of women directors on board is negatively correlated with ROA. This indicates that the firm performance may not be dependent on the number of women directors on board. The results of the study also show that the academic backgrounds of the women board members adds some value toward generating better firm performance. This study contributes to the rising literature on women board member representation based on the firm performance of the top 200 listed companies in Malaysia. The findings encourage public listed companies to appoint women with the necessary qualities as members of the board of directors and to analyse the effects of the diversity policy introduced by the government.